Elaine Steinbeck in USSR - unknown:::Creator::::::::::::
Elaine Steinbeck with two Georgian women sitting around a table at Lochinii Airport in Tbilisi, Georgia, USSR. Photograph taken during the Steinbeck's visit in Oct. 27-31, 1963. Original in safe